OPTIMALKAN CAKUPAN IMUNISASI DASAR LENGKAP MELALUI EDUKASI KEPADA IBU BAYI DI DESA TEMBUNG - Sinaga, Regina Marintan; Riris, Ida Duma; Fransysca, Helena; Sinaga , Nelly Dameria; Simatupang, Lenny Lusia; Banjarnahor, Seriga (Yayasan Penelitian dan Inovasi Sumatera (YPIS), 2025)
Complete basic immunisation is a key public health intervention to prevent infectious diseases in infants. However, immunisation coverage remains suboptimal, particularly due to limited maternal knowledge and negative perceptions. This study aimed to assess the effect of health education on mothers’ attitudes toward complete basic immunisation in Tembung Village, Deli Serdang Regency. A pre-experimental one-group pretest–posttest design was employed, involving 20 mothers with infants, purposively selected from three hamlets with low immunisation coverage. The intervention consisted of interactive health education addressing the benefits, schedule, and common post-immunisation reactions. Maternal attitudes were measured using structured questionnaires before and after the intervention and analysed descriptively. The results demonstrated an improvement in positive attitudes across all indicators following education, including acceptance of immunisation despite concerns about side effects and access barriers. These findings indicate that community-based health education effectively enhances maternal acceptance of immunisation. Nevertheless, short-term evaluation may be subject to social desirability bias, underscoring the need for sustained, repeated educational interventions.